2008
DOI: 10.1038/sj.bjc.6604097
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after curative gastrectomy for gastric cancer in a randomised controlled trial

Abstract: Quality of life (QOL) was studied in gastric cancer patients treated on a randomised, controlled trial comparing D1 (level 1) with D3 (levels 1, 2 and 3) lymphadenectomy. A total of 221 patients were randomly assigned to D1 (n ¼ 110) and D3 (n ¼ 111) surgery. Quality-of-life assessments included functional outcomes (a 14-item survey about treatment-specific symptoms) and health perception (Spitzer QOL Index) was performed before and after surgery at disease-free status. Patients suffered from irrelative events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 27 publications
(31 reference statements)
4
53
0
1
Order By: Relevance
“…However, most of them compared the QoL of gastric cancer patients by the surgical approach only. For example, they compared QoL by different levels of lymph node dissections or by different techniques (17)(18)(19). Few studies have examined the QoL of long-term survivors from gastric cancer using the EORTC QLQ-C30 and QLQ-STO22.…”
Section: Resultsmentioning
confidence: 99%
“…However, most of them compared the QoL of gastric cancer patients by the surgical approach only. For example, they compared QoL by different levels of lymph node dissections or by different techniques (17)(18)(19). Few studies have examined the QoL of long-term survivors from gastric cancer using the EORTC QLQ-C30 and QLQ-STO22.…”
Section: Resultsmentioning
confidence: 99%
“…All patients in our study had undergone radical surgery before they commenced adjuvant treatment. Several research groups, using a variety of instruments [Short Form (SF-36) Health Survey, D15, Spitzer Quality of Life Index, eortc qlq-C30 and -STO22], have reported a reduction in qol in similar populations [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 3-6 months 10,11,22 are needed to achieve the preoperative quality of life after major abdominal surgery. We further considered that some patients would have chemotherapy (usually for 6 months in the adjuvant setting starting within 2 months after surgery).…”
Section: Outcomes and Follow-upmentioning
confidence: 99%